Program Pengabdian Kemasyarakatan: Optimalisasi Pembelajaran Nahwu melalui Kitab Al Miftah di Pesantren Motivator Qur'an Darussalam Klaseman - Ainur Rofiq Sofa; Irma Erviana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Arabic language learning, particularly the study of nahwu, is crucial in understanding Islamic religious texts such as the Qur'an and Hadith. However, in many pesantren (Islamic boarding schools), the teaching and application of nahwu often face various challenges. Therefore, this community service program aims to optimize nahwu learning at Pesantren Motivator Qur'an Darussalam Klaseman by using the Al Miftah book as the main teaching material. This program involves intensive guidance for the students in learning nahwu rules, with an interactive and hands-on approach. The results of this activity show an improvement in the students' understanding and application of nahwu rules, which positively impacts their ability to comprehend Arabic texts, particularly in reading the Qur'an.